Cerebral Concussion Primes the Lungs for Subsequent Neutrophil-Mediated Injury. Issue 9 (September 2018) - Humphries, Duncan C.; O'Neill, Stephen; Scholefield, Emma; Dorward, David A.; Mackinnon, Alison C.; Rossi, Adriano G.; Haslett, Christopher; Andrews, Peter J. D.; Rhodes, Jonathan; Dhaliwal, Kevin
Abstract : Objectives: Mild traumatic brain injury in the form of concussion is extremely common, and the potential effects on pulmonary priming have been underestimated. The aim of this study was to characterize the pulmonary response following mild traumatic brain injury and assess the pulmonary susceptibility to lung injury after a subsequent innocuous pulmonary insult. Design: Experimental in vivo study. Setting: University research laboratory. Subjects: Male CD1 mice. Interventions: We developed a model of concussive traumatic brain injury in mice followed by pulmonary acid microaspiration. To assess the dependent role of neutrophils in mediating pulmonary injury, we specifically depleted neutrophils. Measurements and Main Results: Lateral fluid percussion to the brain resulted in neuronal damage and neutrophil infiltration as well as extensive pulmonary interstitial neutrophil accumulation but no alveolar injury. Following subsequent innocuous acid microaspiration, augmented alveolar neutrophil influx led to the development of pulmonary hemorrhage that was reduced following neutrophil depletion. Conclusions: This model shows for the first time that innocuous acid microaspiration is sufficient to induce neutrophil-mediated lung injury following mild concussion and that the extracranial effects of mild traumatic brain injury have been underestimated. Abstract : Supplemental Digital Content is available in the text.